Explicit renegotiation in repeated games - Mikhail Safronov; Bruno Strulovici (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2014)
Cooperative concepts of renegotiation in repeated games have typically assumed that Paretoranked equilibria could not coexist within the same renegotiation-proof set. With explicit renegotiation, however, a proposal to move to a Pareto-superior equilibrium can be deterred by a different continuation equilibrium which harms the proposer and rewards the refuser. This paper introduces a simple protocol of renegotiation for repeated games and defines the stability of social norms and renegotiation-proof outcomes in terms of a simple equilibrium refinement. We provide distinct necessary and sufficient conditions for renegotiation-proofness, which converge to each other as renegotiation frictions become negligible. Renegotiation-proof outcomes always exist and can be all included within a single, most permissive social norm that is straightforward to characterize graphically.
Keywords: 330